SOME ENGINEERING PROPERTIES OF PROSOPIS AFRICANA PODS RELEVANT TO DEHULLING (Nigerian Journal of Technology, 2003)
Some physical and rheological characteristics of prosopis  africana pods that are pertinent to post-harvest technology were determined. The results obtained indicated that the pods have major diameter ranging from 55mm to 200mm while the geometric mean diameter ranges between 41 mm and 63mm. The values obtained for the density revealed that it could be separated from other agricultural materials that are heavier than water by flotation method. The results obtained further revealed that the energy required to get the seeds from the pods is considerably greater when cracked along its major axis than cracking the pod along its intermediate or minor axis.